2020
DOI: 10.5152/ejbh.2019.5187
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of the Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratio in Patients with Recurrent Idiopathic Granulomatous Mastitis

Abstract: Objective:The aim of this study was to investigate the relationship between the inflammatory parameters including neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) and the prognosis of idiopathic granulomatous mastitis (IGM). Materials and methods:In this retrospective study, a total of 41 patients with IGM who had no malignant disease or inflammatory pathologies were included between January 2010 and December 2017. The patients were divided into two groups according to presence or ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
2
12
1
Order By: Relevance
“…Our results showed that these parameters have a significant effect on the recurrence of the disease. Similarly to our results, Çetinkaya et al [ 42 ] demonstrated that increased preoperative NLR (cut-off value of 5.02) was indicated as a recurrence predictor in patients with IGM recurrence. Kargin et al [ 43 ] reported recurrence in four (20%) patients who received steroid treatment, while recurrence was observed in three (7.9%) patients who received surgical treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed that these parameters have a significant effect on the recurrence of the disease. Similarly to our results, Çetinkaya et al [ 42 ] demonstrated that increased preoperative NLR (cut-off value of 5.02) was indicated as a recurrence predictor in patients with IGM recurrence. Kargin et al [ 43 ] reported recurrence in four (20%) patients who received steroid treatment, while recurrence was observed in three (7.9%) patients who received surgical treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, the use of hematological indexes, such as NLR, monocyte–to lymphocyte ratio (MLR), and PLR, as simple and inexpensive biomarkers for the demonstration of systemic inflammation, has been increasing. Çetinkaya et al [ 42 ] investigated 41 IGM patients with a mean follow-up time of 28.4 months. These results demonstrated that an increased NLR was predictive of poor outcomes in patients with IGM.…”
Section: Discussionmentioning
confidence: 99%
“…An inflammatory biomarker, neutrophil-to-lymphocyte ratio (NLR), has been identified as a risk factor of recurrence in patients with IGM [ 27 ]. However, serum CRP level was not measured in the above study.…”
Section: Discussionmentioning
confidence: 99%
“…There are a limited number of studies that explore the association between NLR and IGM. In 2020, Çetinkaya et al examined the predictive value of NLR and platelet lymphocyte ratio (PLR) in patients with recurrent IGM [5]. They found that the use of NLR seems to be cost-effective and is a promising indicator for the prognosis and recurrence of IGM.…”
Section: Discussionmentioning
confidence: 99%
“…NLR has been used as a diagnostic marker recently for infections accompanied by systemic inflammation [4]. In the literature, there are a limited number of studies investigating the relationship between IGM and inflammatory markers, and these studies focused specifically on the recurrence of IGM [5,6]. Unfortunately, there are no studies about diagnostic tools that can be used for the differential diagnosis of IGM and BA.…”
Section: Introductionmentioning
confidence: 99%